Health care system reform. Ontario family physicians' reactions. - Cohen, M. (2001)
OBJECTIVE: To determine the effect on a cohort of family physicians of health care system reforms in Ontario and the relationship of reforms to their career satisfaction. DESIGN: Follow-up survey in 1999 of a cohort initially studied in 1993, posing many of the original questions along with some new ones. Four focus groups of other Ontario family physicians. SETTING: Family practices in Ontario. PARTICIPANTS: All family physicians who had received certification after completing a family medicine residency between 1989 and 1991 and were practising in Ontario in 1993. This report addresses only those members of the cohort who continued to practise family medicine in Ontario (N = 236). Four focus groups with a total of 27 family physicians. MAIN OUTCOME MEASURES: Reaction to health care system reforms. Perceived effect of reforms on practice. Current perception of quality of health care system and level of career satisfaction and changes in these variables since 1993. RESULTS: Response rate was 53% of original cohort. Only three of 13 selected health reforms were believed to have had a favourable effect. Physicians reported lower levels of satisfaction with their careers. Overall quality of the health care system was perceived by both respondents and focus group members to have declined. Several difficulties affected practice and personal life. CONCLUSION: Family physicians viewed the effect of health care reforms negatively and were significantly less satisfied with their careers than they were in 1993. Better consultation with stakeholders before implementation of reforms is needed to ensure that these stakeholders understand the likely effects of these reforms.